2010
DOI: 10.1002/ijc.25146
|View full text |Cite
|
Sign up to set email alerts
|

Muscle atrophy in experimental cancer cachexia: Is the IGF‐1 signaling pathway involved?

Abstract: Skeletal muscle wasting, one of the main features of cancer cachexia, is associated with marked protein hypercatabolism, and has suggested to depend also on impaired IGF-1 signal transduction pathway. To investigate this point, the state of activation of the IGF-1 system has been evaluated both in rats bearing the AH-130 hepatoma and in mice transplanted with the C26 colon adenocarcinoma. In the skeletal muscle of tumor hosts, the levels of phosphorylated (active) Akt, one of the most relevant kinases involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
87
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 80 publications
13
87
3
1
Order By: Relevance
“…This protein complex, normally associated with the maintenance of muscle mass and muscle hypertrophy could be activated by the increase in amino acids released as a result of increased protein breakdown by the proteasome (41). In a murine model of cancer cachexia, increased levels of phosphorylated Akt and increased expression of IGFI in muscle of tumor-bearing AH-130 and C26 mice suggests that muscle wasting in tumor-bearing animals may not be associated with downregulation of molecules involved in the anabolic response (42). In further support of a counterregulatory response to compensate for muscle loss in cachexia, Op den Kamp and colleagues (43) have recently observed increased Akt phosphorylation in the muscle of patients with cachectic lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This protein complex, normally associated with the maintenance of muscle mass and muscle hypertrophy could be activated by the increase in amino acids released as a result of increased protein breakdown by the proteasome (41). In a murine model of cancer cachexia, increased levels of phosphorylated Akt and increased expression of IGFI in muscle of tumor-bearing AH-130 and C26 mice suggests that muscle wasting in tumor-bearing animals may not be associated with downregulation of molecules involved in the anabolic response (42). In further support of a counterregulatory response to compensate for muscle loss in cachexia, Op den Kamp and colleagues (43) have recently observed increased Akt phosphorylation in the muscle of patients with cachectic lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…33 The above PBM indicated that IGF-1 might promote the myoblast proliferation in hG to establish the hPlSH in which the FOXO3a is the same as in the nPlSH, and it might also promote myoblast proliferation in its nPlSH might be upgraded by IGF-1 upregulation and FOXO3a downregulation. Penna et al 34 have hyperexpressed IGF-1 by gene transfer in the tibialis muscle of the C26 hosts. In healthy animals, they found that IGF-1 overexpression markedly increased both¯ber and muscle size.…”
Section: Insulin-like Growth Factor-1 and Forkhead Box O Family 3amentioning
confidence: 99%
“…The other way round, inhibition of this pathway was reported in conditions characterized by muscle wasting such as denervation, aging, disuse, or glucocorticoid treatment, and its restoration by means of IGF-1 administration or IGF-1 local hyperexpression is able to prevent or correct muscle depletion (reviewed in Glass, 2010). An exception, in this regard, is experimental cancer cachexia, where the PI3K/Akt/mTOR pathway is not down-regulated (Acharrya et al, 2005;Penna, Bonetto et al, 2010), and muscle atrophy cannot be prevented by both IGF-1 administration or its hyperexpression in the skeletal muscle (Costelli et al, 2006;Penna, Bonetto et al, 2010).…”
Section: Tissue Wasting In Cachexia: Hypoanabolism or Hypercatabolism?mentioning
confidence: 99%
“…Such a strategy appears to work perfectly well in several experimental models of muscle wasting including denervation, amyotrophic lateral sclerosis, disuse (reviewed in Glass, 2010). However, it is useless in experimental cancer cachexia, where, despite high protein breadown rates occur, the insulin/IGF-1 pathway is not down-regulated, protein synthesis rates are only slightly reduced or even unchanged, and the protein synthetic signaling is poised into the activated state (Costelli et al, 1993;Penna, Bonetto, et al, 2010;Aversa et al, 2012).…”
Section: Strategies To Correct Metabolic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation